Evidence for the multiple hits genetic theory for inherited language impairment: a case study - Centanni, Tracy M.; Green, Jordan R.; Iuzzini-Seigel, Jenya; Bartlett, Christopher W.; Hogan, Tiffany P. (Frontiers in Genetics, 2015)
Communication disorders have complex genetic origins, with constellations of relevant gene markers that vary across individuals. Some genetic variants are present in healthy individuals as well as those affected by developmental disorders. Growing evidence suggests that some variants may increase susceptibility to these disorders in the presence of other pathogenic gene mutations. In the current study, we describe eight children with specific language impairment and four of these children had a copy number variant in one of these potential susceptibility regions on chromosome 15. Three of these four children also had variants in other genes previously associated with language impairment. Our data support the theory that 15q11.2 is a susceptibility region for developmental disorders, specifically language impairment.